Enzymatic Asymmetric Reduction of Unfunctionalized C=C Bonds with Archaeal Geranylgeranyl Reductases. (22nd July 2021) - Cervinka, Richard; Becker, Daniel; Lüdeke, Steffen; Albers, Sonja‐Verena; Netscher, Thomas; Müller, Michael
Abstract: The asymmetric reduction of activated C=C bonds such as enones is well established for non‐enzymatic methods as well as in biocatalysis. However, the asymmetric reduction of unfunctionalized C=C bonds is mainly performed with transition metal catalysts whereas biocatalytic approaches are lacking. We have tested two FAD‐dependent archaeal geranylgeranyl reductases (GGR) for the asymmetric reduction of isolated C=C bonds. The reduction of up to four double bonds in terpene chains with different chain lengths and head groups was confirmed. Methyl‐branched E ‐alkenes were chemoselectively reduced in the presence of cyclic, terminal or activated alkenes. Using a removable succinate "spacer", farnesol and geraniol could be quantitatively reduced (>99 %). The reduction is strictly ( R )‐selective (enantiomeric excess >99 %). Hence, GGRs are promising biocatalysts for the asymmetric reduction of unactivated isolated C=C bonds, opening new opportunities for the synthesis of enantiopure branched alkyl chains. Abstract : Archaeal geranylgeranyl reductases were tested for the biocatalytic asymmetric reduction of isolated unfunctionalized C=C bonds. The reduction of acyclic terpene chains with different head groups showed great tolerance for substrates, without affecting cyclic or terminal C=C bonds. Moreover, the introduction of a succinate hemiester significantly increased conversion. The reaction is highly diastereo‐ and enantioselective ( ee >99 %).